Peran Penting Keselamatan dan Kesehatan Kerja terhadap Kinerja Karyawan (Studi Kasus: PT. PLN ULP Soppeng) - Abbas, Subhan Akbar; Chaeruddin, Chaeruddin (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Employee performance constitutes a critical dimension within an organizational context; the advantageous ramifications of optimal employee performance can yield significant long-term benefits for the organization. Performance is a variable that is susceptible to influence by a myriad of factors, with one notable element being occupational safety and health. The objective of this investigation was to elucidate the relationship between occupational safety and health and the performance of employees at PT. PLN ULP Soppeng. This research employed a quantitative methodology, applying multiple linear regression analysis to ascertain the correlation or effect between the independent and dependent variables. The sample for this analysis comprised 22 employees from PT. PLN ULP Soppeng. Data collection was executed utilizing a questionnaire instrument designed to encompass the three variables under examination in the study. The findings from this research indicated a statistically significant influence of occupational health on employee performance. Conversely, the variable of occupational safety did not demonstrate a significant effect on employee performance. This study was confined to a singular locale; future research endeavors would benefit from a comparative analysis that assesses the impact of identical variables across diverse locations, as well as investigates various additional factors that may exert influence on employee performance.